Consideration of Cytokines as Therapeutics Agents or Targets - Xing, Z.; Wang, J. (Current Pharmaceutical Design, 2000)
There has been an explosion of our knowledge in cytokine biology in the last decade. Such knowledge is being quickly translated into the identification of etiologies and improved prophylaxis and therapy of disease. While cytokines have the potential to be used as therapeutics or immune adjuvants for certain diseases, they may also be culprits as therapeutic targets in other diseases. This review article servesas an introduction to the other five articles in this thematic issue each of which has a specific focus on the frontier of cytokine therapeutic biology. This review contains sections dealing with general cytokine properties, cytokine classifications, human conditions caused by cytokine under-expression and over-expression, Th1 and Th2 paradigm, cytokine therapy for acute/chronic inflammatory conditions, cytokine therapy for infectious diseases, and cytokine therapy for cancer.
Keywords: therapy